PUSAT TERAPI ANAK AUTIS DI MARTAPURA KALIMANTAN SELATAN - Rahman, Erinna Salsabilla Ardafi; Wastuty, Prima Widia (JURNAL TUGAS AKHIR MAHASISWA LANTING, 2023)
During the period of cognitive development, some children not a few who experience some problems at the stage of their cognitive development, one of which is the presence of Autism Spectrum Disorder (ASD). It was recorded in January 2018 that there were 500 cases of children with autism in South Kalimantan. In South Kalimantan itself, therapy centers for autistic children are still very few and the facilities they provide are still very limited. And there are still many parents who think therapy for autistic children doesn't make any changes to their children. Meanwhile, in therapy it takes a long time and consistently in therapy and the active cooperation of parents must be active at home. So it is felt that there is a need for an Autistic Children Therapy Center in South Kalimantan at this time. This is realized by the method of Psychological Architecture and the concept of applying the principles of Healing Environment to create an Autistic Child Therapy Center that can improve the behavior of autistic children for the better and provide education to parents.